2014
DOI: 10.1186/preaccept-2774583901252502
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of clinical tests in the diagnosis of anterior cruciate ligament injury: a systematic review

Abstract: Background: Numerous clinical tests are used in the diagnosis of anterior cruciate ligament (ACL) injury but their accuracy is unclear. The purpose of this study is to evaluate the diagnostic accuracy of clinical tests for the diagnosis of ACL injury. Methods: Study Design: Systematic review. The review protocol was registered through PROSPERO (CRD42012002069). Electronic databases (PubMed, MEDLINE, EMBASE, CINAHL) were searched up to 19th of June 2013 to identify diagnostic studies comparing the accuracy of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The diagnostic accuracy of the other ACL tests is well established in multiple meta-analyses and systematic reviews. 1,9,16,18,19,21 In accordance with the current study, the Lachman test appears to have the highest diagnostic accuracy overall, while the pivot-shift test has the highest specificity but low sensitivity. However, the low diagnostic accuracy of the anterior drawer test is in contrast with the high specificity in the current study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The diagnostic accuracy of the other ACL tests is well established in multiple meta-analyses and systematic reviews. 1,9,16,18,19,21 In accordance with the current study, the Lachman test appears to have the highest diagnostic accuracy overall, while the pivot-shift test has the highest specificity but low sensitivity. However, the low diagnostic accuracy of the anterior drawer test is in contrast with the high specificity in the current study.…”
Section: Discussionsupporting
confidence: 88%
“…9 The included articles in the meta-analyses and systematic reviews were of low-level evidence because of different observational designs with diverse patient populations, resulting in a large interstudy heterogeneity. 16,19 A difference between the current study when compared with other studies is the recruitment of patients. The majority of studies in the literature only reported physical examination findings of patients with known ACL injuries based on MRI or an arthroscopic examination.…”
Section: Discussionmentioning
confidence: 89%
“…[ 8 ] On the other hand, arthroscopy is another diagnostic method which allows direct visualization of all intra-articular structures. [ 9 ] But this method is relatively expensive and invasive [ 10 ], therefore, finding a new method or new procedure with high diagnostic value in evaluating ACL injury is needed. Tackling this issue, Kosaka et al demonstrated that a new method was not needed, as MRI accuracy can be increased by using a different view of knee lesions such as ACL injury.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral compartment translation and the tibial acceleration Please see "Appendix" section for the Pivot Study Group members. physical examination, instrumented testing, diagnostic imaging, and arthroscopic findings [5,27,47,52].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical identification of an ACL lesion is based on several physical examination tests [2,15,17,25,48,52], each one with its own specificity and sensitivity [5,21,52]. The most commonly used tests are designed to evaluate the knee laxity in the sagittal plane and include the Lachman and anterior drawer [15,17,19,35,50].…”
Section: Introductionmentioning
confidence: 99%